Work in deregulated labour markets: a research agenda for precariousness - Pulignano, Valeria (Brussels, 2019)
"This Working Paper tackles two questions: what counts as work within a deregulated labour market; and what are the implications for the study of precariousness? The paper addresses the traditional dichotomy between paid and unpaid work which obscures how unpaid activities often undercut paid employment. In this light, it suggests a new way of understanding precariousness which can help trade unions to understand it and tackle its increasingly prevalence. "